IMMERGING SOLUTION (PULSING) ON Chrysanthemum CUTTING FLOWER - Agnesia Yolanda Soleman; Bobby J.V. Polii (Sam Ratulangi University, 2020)
Post-harvest handling is important to increase vase life and maintain the freshness of cut chrysanthemums. Cut flowers are very sensitive to physical and chemical damage, and pathogenic infections, and pest attacks during and after harvest. Supplementation of water and nutrients from outside is used as an additional source of energy for the survival of the flowers after harvesting. The role of a freshener solution in cut flowers is to provide a nutritional replacement after the flowers are cut from the parent plant so that their freshness can be maintained. The main component that must be present in the preservative solution is sugar as an energy source for metabolic processes, acidic substances such as citric acid are used to reduce the pH of the solution to 3 - 4.5 so as to increase the absorption of the solution by cut flower stalks, and the addition of germicides for antibacterial.Keywords: Flower; soaking; Chrysanthemum; Post-harvestAbstrakPenanganan pascapanen sangat penting untuk meningkatkan vase life dan mempertahankan kesegaran krisan potong. Bunga potong sangat peka terhadap kerusakan fisik maupun kimia, dan infeksi patogen serta serangan hama selama dan setelah panen. Pemberian pengganti air dan nutrisi dari luar digunakan untuk tambahan sumber energi bagi kelangsungan hidup bunga setelah pemanenan. Peranan larutan penyegar pada bunga potong adalah untuk memberikan pengganti nutrisi setelah bunga dipotong dari induk tanaman sehingga kesegarannya dapat dipertahankan. Komponen utama yang harus ada dalam larutan pengawet adalah gula sebagai sumber energi untuk berlangsungnya proses metabolisme, zat pengasam seperti asam sitrat digunakan untuk menurunkan pH larutan menjadi 3 - 4,5 sehingga dapat meningkatkan penyerapan larutan oleh tangkai bunga potong, serta penambahan germisida untuk antibakteri.Kata kunci: Bunga; perendam; Chrysanthemum; Pascapanen